Correlation of Carotid Intimomedial Thickness with Coronary Risk Factors in Type 2 Diabetic Patients - Shukla, Avikal (Journal of Nepalgunj Medical College, 2017)
Aims: To compare the carotid intima-media thickness in type 2 diabetic patients with and without coronary artery disease (CAD), and to correlate the intima-media thickness (IMT) with known coronary risk factors. Methods: two hundred and twenty patients of type 2 diabetes were recruited for the study. History and physical examination were recorded. Laboratory investigations included fasting and 2-hour post-prandial blood sugar , blood urea, serum creatinine, lipid profile, glycated haemoglobin, and microalbuminuria. Ultrasonographic scanning of the carotid arteries was performed to measure the carotid IMT. For identification of cases of silent ischaemia, treadmill test (TMT) was performed. Results: The study group was divided into a non-CAD group (n=80), and a CAD group (n=140). The mean carotid IMT of the group as a whole, was 0.840±0.2 mm. The mean carotid IMT was significantly higher (p<0.0001) in type 2 diabetics with CAD (both overt and silent) than in those without CAD. In diabetics with CAD, the systolic blood pressure, diastolic blood pressure and triglycerides were found to be predictors of high mean carotid IMT. On subgroup analysis of the cases with silent ischaemia, the variables affecting carotid IMT were serum creatinine, total cholesterol, microalbuminuria/proteinuria, serum triglyceride levels, and diastolic blood pressure. Conclusion: A high carotid IMT is a surrogate and reliable marker of higher risk of CAD amongst type 2 diabetic patients, even in those without overt CAD. The study underlines the utility of carotid IMT as a simple, non-invasive, safe, and cheap screening test for the assessment of risk/prognosis of CAD in type 2 diabetics. We have also demonstrated the usefulness of measuring IMT, as a means to detect silent CAD among type 2 diabetics. JNGMC Vol. 13 No. 2 December 2015, Page: 25-30